Key Opinion Leader (KOL) in Influencing Customer’s Buying Decision on Fashion Products through Instagram - Pratama, Dendi Andi (APPS Publications, 2024)
Objective This study aims to assess the impact of key opinion leader, intention to interact, and intention to follow the advice on purchase intention. Methodology To collect the sample data, this research using online questionnaire and get 131 respondents who has Instagram account and looked at influencer accounts for fashion references. The collected data was analysed by Structural Equation Model (SEM) using Smart PLS 3. Findings The result shows that Key opinion leader have a direct and indirect affect through consumer behavior such as intention to follow the advice and intention to interact as mediator to purchase intention. Novelty Investigating the mediating role of intention to interact and intention to follow the advice in the relationship between key opinion leader and purchase intention.